Penyederhanaan Proses Legalisasi Apostille - Astuti B, Isma Widya; Sakharina, Iin Karita; Aswan, Muhammad (Universitas Widya Gama Malang, 2023)
This study aims to analyze the role of the apostille as an effort to simplify the stages of the process of legalizing public documents, and to analyze legal certainty for public documents that have been legalized by apostille. This research is an empirical research, where the data is qualified as primary and secondary data. Primary data was obtained through interviews, and secondary data was obtained through literature studies. The data collected is then processed using a qualitative analysis approach. The results of the study show that the role of the Apostille as an effort to simplify the stages of the process of legalizing public documents has made it easy for Indonesian citizens to use their public documents abroad. This convenience saves time, costs and is much easier than the conventional legalization of public documents for going abroad, the process of which must go through various parties. Apostille services only need to go through the Ministry of Law and Human Rights as a certified authority. In Indonesia, the Competent Authority appointed and competent to issue Apostille is the Ministry of Law and Human Rights (KumHAM). And then th e legal certainty of public documents that have been legalized Apostille is the guarantee that public documents that have been legalized Apostille will be recognized and accepted by all countries that have ratified the Apostille Convention. This certainly makes it easy for the public to legalize public documents that will be used abroad or vice versa.